Indonesian Learners' Self-Directed Learning in Online EAP Classes: Its Manifestations and Factors - Subekti, Adaninggar Septi (LITERA, 2021)
The present study was conducted to investigate online English for Academic Purposes (EAP) classes' learners' manifestations of the level of their Self-directed Learning (SDL) in English as well as their views about possible factors influencing their SDL. The study used interviews as the method of data collection. Six EAP learner participants at the university level participated in the study. Through Thematic Analysis of the interview transcripts, the present study found that learners with a high SDL (HSDL) adhered to a carefully planned learning agenda and were eager to learn more. In comparison, learners with a low SDL (LSDL) reported having no deliberate planning for learning and making no or little effort to learn English independently outside English class. The present study further found that perceived relevance of English class increased learners' SDL, and its lack of relevance reduced it. The study also found that LSDL learners' sense of achievement and teachers' support could increase their interest in learning, and so their SDL. Based on the findings, it was suggested that EAP courses increase their relevance to learners' needs and teachers provide the necessary support for LSDL learners to make them more interested in learning and increase their SDL.